Aldosterone controls primary cilium length and cell size in renal collecting duct principal cells. Issue 2 (19th December 2019) - Komarynets, Olga; Chassot, Alexandra; Bernabeu, Eva; Czogalla, Jan; Roth, Isabelle; Liaudet, Nicolas; Prodon, François; Loffing, Johannes; Feraille, Eric
Abstract: Primary cilia are nonmotile sensory organelles found on the surface of almost all kidney tubule epithelial cells. Being exposed to the tubular lumen, primary cilia are thought to be chemo‐ and mechanosensors of luminal composition and flux, respectively. We hypothesized that, Na + transport and primary cilia exist in a sensory functional connection in mature renal tubule epithelial cells. Our results demonstrate that primary cilium length is reduced in mineralocorticoid receptor (MR) knockout (KO) mice in a cell autonomous manner along the aldosterone‐sensitive distal nephron (ADSN) compared with wild type (as µm ± SEM; 3.1 ± 0.2 vs 4.0 ± 0.1). In mouse cortical collecting duct (mCCD)cl1 cells, which are a model of collecting duct (CD) principal cells, changes in Na + transport intensity were found to mediate primary cilium length in response to aldosterone (as µm ± SEM: control: 2.7 ± 0.9 vs aldosterone treated: 3.8 ± 0.8). Cilium length was positively correlated with the availability of IFT88, a major intraflagellar anterograde transport complex B component, which is stabilized in response to exposure to aldosterone treatment. This suggests that the abundance of IFT88 is a regulated, rate limiting factor in the elongation of primary cilia. As previously observed in vivo, aldosterone treatment increased cell volume of cultured CD principal cells. Knockdown of IFT88 prevents ciliogenesis and inhibits the adaptive increase in cell size that was observed in response to aldosterone treatment. In conclusion, our results reveal a functional connection between Na + transport, primary cilia, and cell size, which may play a key role in the morphological and functional adaptation of the CD to sustained changes in active Na + reabsorption due to variations in aldosterone secretion.